Truncated 21st-century trajectories of progressive international solidarity. Issue 7 (10th November 2019) - Bond, Patrick
ABSTRACT: What potentials exist for realizing a new internationalism consistent with the visions of Samir Amin, Africa's greatest political economist and one of the leading Marxists of his generation? To answer requires tracing back several decades, to interpret Amin's own strategy for establishing first, continental and then, global networks mixing radical scholars and activists. Many missteps were taken, among which were gaps between top-down intellectual formulations (and manifestos) and bottom-up strategic narratives (often lacking a coherent ideology). Because of these limitations, even Amin's most opportune political networking faltered, proving unsustainable. On most such occasions, it was Amin's own auto-critique that assisted his allies in developing more profound formulations. It is in these various initiatives to which Amin generously gave his time, energy, resources and political commitment that we can learn some of the most powerful lessons for future internationalism.